2014
DOI: 10.1016/j.drugalcdep.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Does early socio-economic disadvantage predict comorbid alcohol and mental health disorders?

Abstract: Please cite this article as: Salom, C.L., Williams, G.M., Najman, J.M., Alati, R.,Does early socio-economic disadvantage predict comorbid alcohol and mental health disorders?, Drug and Alcohol Dependence (2014), http://dx.doi.org/10. 1016/j.drugalcdep.2014.06.011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Little et al . and other several studies [6,40,49,52,58–60]). Longitudinal studies suggest that the association between QOL and alcohol use might be due to these covariates.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Little et al . and other several studies [6,40,49,52,58–60]). Longitudinal studies suggest that the association between QOL and alcohol use might be due to these covariates.…”
Section: Introductionmentioning
confidence: 63%
“…There are also well-established associations between patterns of alcohol use and various young adult sociodemographic characteristics (e.g. Little et al and other several studies [6,40,49,52,[58][59][60]). Longitudinal studies suggest that the association between QOL and alcohol use might be due to these covariates.…”
Section: Qol and Alcohol Use In Young Adulthoodmentioning
confidence: 87%
“…For example, Lee and colleagues (2013) found high school graduation was related to the co-occurrence of mental health and substance abuse disorder symptoms in young adulthood while Salom and colleagues (2014) provided evidence that prenatal socioeconomic disadvantage predicted comorbid alcohol and mental disorders at age 21. In a previous research paper using data from the Woodlawn study, Green and colleagues (2012) found that mother’s education measured in childhood differentiated those with comorbid substance use and depressive disorders compared to those with depression without a substance use disorder, but dropping out of high school only distinguished those with a substance use disorder without depression from those with depression without a substance use disorder and from those with neither condition.…”
Section: Discussionmentioning
confidence: 99%
“…Membership in lower social classes has been associated with a variety of mental health risk factors. Lower‐social class individuals are two to five times more likely to experience a diagnosable mental health condition than the general population (Bourdon, Rae, Locke, Narrow & Regier, ); and more likely to experience depression (Costa‐Font & Gil, ; Poulton et al., ; Zimmerman & Katon, ), anxiety disorders (Lynch, Kaplan & Salonen, ) and substance use disorders (Diala, Muntaner & Walrath, ; Furr‐Holden & Anthony, ; Green, Carnes, Carnes & Weinman, ; Salom, Williams, Najman & Alati, ; Swendsen et al., ; Wohlfarth & Van Den Brink, ). In addition, those who seek treatment are more likely to receive lower quality mental health care (DHHS, ; Isaacs & Schroeder, ; McGrath, Keita, Strickland & Russo, ; Pope & Arthur, ), less likely to experience positive outcomes from therapy (Falconnier, ), and more likely to drop out of therapy early (Smith, ; Wierzbicki & Pekarik, ).…”
Section: Introductionmentioning
confidence: 99%